2021
DOI: 10.12800/ccd.v16i49.1609
|View full text |Cite
|
Sign up to set email alerts
|

Revisión sistemática del tiempo de compromiso motor en Educación Física

Abstract: The engagement motor time (EMT) is one of the most taken into account criteria when evaluating a quality Physical Education class. The main objective of this review paper is to collect the average values of EMT in the Physical Education lessons, as well as to highlight the importance of unifying criteria when obtaining and publishing the results. For this purpose, 65 articles are selected in a systematic search using the following databases Dialnet, Google Scholar, Scopus, Redalyc and Pubmed. The results show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
0
5
0
4
Order By: Relevance
“…This is where the dilemma of how much time and performance is spent on the task can come in. It has been shown that the time spent in physical education classes is insufficient 28 and that it is necessary to carry out physical activity and sport outside school hours.…”
Section: Discussionmentioning
confidence: 99%
“…This is where the dilemma of how much time and performance is spent on the task can come in. It has been shown that the time spent in physical education classes is insufficient 28 and that it is necessary to carry out physical activity and sport outside school hours.…”
Section: Discussionmentioning
confidence: 99%
“…Los modelos que se aplican para la enseñanza de la Educación Física utilizando las TIC se caracterizan por que se constituyen en una especie de constructo que tanto docentes como estudiantes en las distintas universidades tratan de tomar como modelo, para que esta tendencia sea un estímulo para la autoestima de los estudiantes. Martínez-Hita, et al (2021) Revisión sistemática del tiempo de compromiso motor en Educación Física. Cultura, Ciencia y Deporte.…”
Section: Autores Y Temas Aplicaciones De Las Tic En La Enseñanza De L...unclassified
“…A pesar de las buenas intenciones desde la asignatura de EF (Wong et al, 2021), las limitaciones temporales establecidas por el currículo impiden contrarrestar, al menos de manera notoria, esta tendencia. Una revisión reciente acerca del tiempo de compromiso motor en las clases de EF hace referencia a que solo un 36.35% del tiempo de la sesión los alumnos se encuentran en movimiento (Martínez-Hita et al, 2021). Este dato, similar al de otras revisiones tanto en Primaria (Hollis et al, 2017) como en Secundaria (Hollis et al, 2020), junto a las escasas horas lectivas semanales del área, obliga a los docentes de EF a buscar alternativas motivadoras para alcanzar las recomendaciones de AF propuestas por la OMS.…”
Section: Discusión Y Conclusionesunclassified